2005
DOI: 10.1111/j.1365-2222.2005.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of asthma attacks and emergency visits among asthma patients with allergic rhinitis: a subgroup analysis of the improving asthma control trial

Abstract: Presence of self-reported concomitant AR in patients with asthma resulted in a higher rate of asthma attacks and more emergency room visits compared with asthma patients without concomitant AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(112 citation statements)
references
References 24 publications
(39 reference statements)
6
102
0
4
Order By: Relevance
“…Rhinitis has been shown to be associated with the lack of asthma control. 8,37 This association was not significant with the multidimensional asthma control classification, and heterogeneous results were observed for the 1-dimensional aspects.…”
Section: Discussionmentioning
confidence: 52%
“…Rhinitis has been shown to be associated with the lack of asthma control. 8,37 This association was not significant with the multidimensional asthma control classification, and heterogeneous results were observed for the 1-dimensional aspects.…”
Section: Discussionmentioning
confidence: 52%
“…Several other studies confirm the link of comorbid A+AR with increased resource utilization and costs [9, 11, 12]. However, when AR is diagnosed and properly treated, not only are symptoms alleviated, but additional benefits may occur through a reduction of asthma-related complications [13,14,15,16], and potentially through an improved quality of life.…”
Section: Introductionmentioning
confidence: 92%
“…First, regarding asthma severity, self-reported concomitant allergic rhinitis results in more frequent emergency room visits and asthma attacks in patients with chronic asthma [8]. Another retrospective study showed that asthmatics with concomitant allergic rhinitis visited general practitioners more frequently, had more asthma-related hospitalizations, and had higher asthma-related medication costs than those without [9].…”
Section: Discussionmentioning
confidence: 99%
“…Allergic rhinitis often precedes the development of asthma [4,5,6,7], suggesting that it may be a risk factor for asthma. The presence of concomitant allergic rhinitis in asthmatics results in more frequent asthma attacks, emergency room visits [8], and asthma-related hospitalizations [9], as well as higher asthma-related medication costs [9,10]. Nonasthmatics with allergic rhinitis have elevated numbers of eosinophils in the bronchial mucosa [11,12,13].…”
Section: Introductionmentioning
confidence: 99%